Managing systemic banking crises - Hoelscher, David S. (IMF WashingtonUS, 2003)
Discusses the causes of a systemic banking crisis, its costs, and the crisis management strategy. Describes the initial crisis containment stage, bank restructuring, and management of non-performing loans and corporate debt restructuring. Looks at linkages between bank restructuring and macroeconomic policies.